Effects of the Zishen Yutai Pill compared with placebo on pregnancy outcomes among women in a fresh embryo transfer cycle: a Post Hoc subgroup analysis of a randomized controlled trial - Chen, Xiaoli; Li, Yu; Zhou, Jiewen; Wei, Xuemei; Ning, Na; Huang, Qiuling; Pang, Xiufei; Yang, Dongzi (Frontiers in Endocrinology, 2023)
Objective: To assess whether the administration of Zishen Yutai Pill (ZYP) could improve the pregnancy outcomes in different subgroups of women undergoing fresh embryo transfer cycles.This is a post hoc analysis of a large scale, placebo-controlled, double blind, randomized clinical trial (RCT) regarding the use of ZYP during assisted reproductive technology (ART) treatment. The RCT was conducted at 19 IVF centers between April 2014 and June 2017. A total of 2265 women undergoing fresh embryo transfer cycles were randomly assigned in a 1:1 ratio to receive ZYP (n = 1131) or placebo (n = 1134). Post hoc logistic regression analyses were applied in this study to examine the between-group differences of ZYP and placebo on clinical pregnancy rate among different subgroups. Detailed analyses, both in intention-to-treat (ITT) and per-protocol population, were also conducted in specific subgroups with regards to rates of implantation, biochemical pregnancy, clinical pregnancy, live birth, pregnancy loss, as well as other neonatal indices.Results: ZYP showed a significantly higher clinical pregnancy rates than placebo in the ITT population. Detailed subgroup analyses were conducted in subgroup in advanced maternal age (AMA, ≥ 35 years old) and overweight/obese patients (BMI > 24), due to the clinical importance and statistical results. In these subgroups, baseline characteristics were similar between two arms (all P > 0.05). Significantly elevated clinical pregnancy rates were observed in ZYP cohort (both P < 0.05) compared with the placebo group. Results also showed that ZYP treatment resulted in significantly higher rates of implantation, biochemical pregnancy in AMA or overweight/obese patients in ITT analysis (all P < 0.05).The current post hoc subgroup analysis suggested that AMA and overweight/obese women could experience clinical benefits when treated with ZYP in their fresh embryo transfer cycles. The study provides references for the use of ZYP in ART practices. However, further studies in specific subgroups should be examined in more rigorous clinical trial settings.